2018
DOI: 10.5937/ekopolj1801033t
|View full text |Cite
|
Sign up to set email alerts
|

Researching consumer habits regarding food label reading

Abstract: The research on the knowing of the significance and contents of the food product label as well as understanding the data on the label is presented in this paper. The research used the Pearson's chi-square test of homogeneity and Pearson's chi-square test of independence. The research was conducted on a representative sample of 598 respondents from 10 cities in the Republic of Serbia. Research results show that more than half of the respondents always or often read the label, then, that men and women have a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The increasing behavior of paying attention to NKV certification labels was related to an increase in a person's age. Previous research showed that group of people 31 years old and above read nutrition labels more often than younger groups (Çoşkun and Kayışoğlu, 2016;Trandafilović et al, 2018). Likewise, (Ghvanidze et al, 2017) found that people aged 45-54 are more likely to look for information from food labels.…”
Section: Resultsmentioning
confidence: 97%
“…The increasing behavior of paying attention to NKV certification labels was related to an increase in a person's age. Previous research showed that group of people 31 years old and above read nutrition labels more often than younger groups (Çoşkun and Kayışoğlu, 2016;Trandafilović et al, 2018). Likewise, (Ghvanidze et al, 2017) found that people aged 45-54 are more likely to look for information from food labels.…”
Section: Resultsmentioning
confidence: 97%